VUCA-MEASURING CONCEPTUAL FOUNDATIONS IN THE CONTEXT OF PROFESSIONAL SELF-DEVELOPMENT - I. O. NIKONENKO (Вісник: Київський інститут бізнесу та технологій, 2019)
Now, so important to consider the business as a financial and profitability structure, that is interested in competitiveness, efficient activity and economic development. The achievement of the defined indicators of successful business is possible of the presence of professional, experienced and conscientious employees, so is the important to form such a system of personnel management, which is in order to promote the competence of the employees. In addition to making business investments in training and developing competencies of the employees, an important prerequisite is the meaningful and purposeful willingness of the personality to foster the development of herself professional competence in the context of the actual volatile and unpredictable VUCA-world. To that, in the article describe the conceptual foundations of professional personal self-development in the context of the VUCA-world and presented of the basic VUCA-competencies as the competitive advantages of the modern business environment. According to the provisions of the VUCA-world, important competencies of the employees there are: prognostic vision in the context of prospect of business development; understanding of the actual needs and purpose of the business activity; creativity, as the ability to the put forward alternative solutions of the business problems, and  agility, as the ability and the internally determined conviction to act in the interests of the business. The explained of importance of social and area organization as main conditions for the professional self-development, personal awareness and competitiveness of the employees. In the context of the activity approach, the revealed of the importance of the professional environment for the development of the leading competencies of the employe. So, in the article is express of the priority of the psycho-sociology need for the formation of such the model of the development of the competencies of the employee, that would be answer of the needs of actual unpredictable VUCA-world.